Dietary habits and nutritional status of upper primary school children covered under Mid-Day Meal scheme in rural Punjab - Kaur, Harpreet; Halder, Pritam; Srivastava, Rachana; Singh, Tarundeep; Khanna, Poonam (International Journal Of Community Medicine And Public Health, 2024)
Background: The objective of this study was to evaluate the dietary habits and nutritional status of upper primary school children covered under mid-day meal scheme (MDMS) in rural Punjab. Methods: This cross-sectional research was conducted among 336 adolescent (10-15 years) students of 6th to 8th standard randomly selected from 11 government/ municipality schools selected randomly from the total 112 schools rural Punjab in 2018. After taking informed written assent/ consent, pretested, semi structured questionnaire was administered. Anthropometric measurements were taken to establish malnutrition, underweight, stunting, wasting and overweight. Results: Majority (90%) liked the MDMS which was being served to them. There was 96% regularity in attending the school daily with a slightly less emphasis on the cleanliness maintenance (73%) of the children by the schoolteachers. Malnutrition and underweight were 59% and 50% prevalent, respectively. The prevalence of stunting was higher in girls (30%). In boys (154) both the stunting and wasting was 23%, with 5% and 6% prevalence of overweight and at risk of overweight respectively. Whereas in case of girls (182), the prevalence of stunting (30%) was more than wasting (25%) with less girls (3% each) being overweight and at risk of overweight. Conclusions: Regularity and attendance were up to mark due to increased likeliness of the food by majority of the students, though cleanliness should be improved further. Higher prevalence of malnutrition, wasting and stunting was observed which was even higher among girls. Overweight and risk of overweight was higher among boys. Hence, nutritional status was unsatisfactory.